Deposition of Ibuprofen Crystals on Hydroxypropyl Cellulose/Polyacrylamide Gel: Experimental and Mathematic Modeling Releasing. (11th October 2016) - Castillo-Miranda, Claudia Alicia; Beatriz Morales-Cepeda, Ana; Castro-Guerrero, Carlos Fernando; Salas-Papayanopolos, Homero; Velasco-Ocejo, Hugo Alberto; González-Sánchez, Jorge Alberto; Paramo-Garcia, Ulises; De Alva-Salazar, Hugo
Abstract : The crystallization of nonsteroidal anti-inflammatory drug [2-(4-isobutyl-phenyl) propionic acid] ibuprofen (IBP) on a hydroxypropyl cellulose (HPC) and polyacrylamide (PAAm) gel was studied as well as the release kinetics of the drug. The IBP was crystallized on the gel surface of HPC/PAAm. It had a prismatic shape and the growth was made in an aqueous medium; the crystallinity grade of the gels HPC/PAAm and HPC/PAAm-IBU increased to 68% and to 58%, respectively. The release of IBP is performed by two means: by a non-Fickian diffusion process and by relaxation of the chains of the gel; without regard to temperature and the diffusion media, this correlates with the lower critical solution temperature (LCST) of the proposed gel. This polymer matrix provides an option for releasing nonsteroidal anti-inflammatory drugs in a temperature range of 35–39°C. Korsmeyer and Peppas mathematical model was simulated for data releases, statistically significant at 95% confidence level.